Предмет: Алгебра,
автор: wolf43goblin53
Помогите с примерами ( желательно с объяснинием)
Приложения:
Ответы
Автор ответа:
1
(3√10 - √5)² = (3√10)² - 2 · 3√10 · √5 + (√5)² = 9·10 - 6√50 + 5 = 95 - 6·5√2 =
= 95 - 30√2.
√(√7 + 4) · √(4 - √7) = √((√7 + 4)·(4 - √7)) = √(4² - (√7)²) = √(16 - 7) = √9 = 3.
Автор ответа:
1
Похожие вопросы
Предмет: Русский язык,
автор: laczuleyxa01
Предмет: Литература,
автор: wocuno
Предмет: Алгебра,
автор: kykymber228
Предмет: Математика,
автор: Нафаня1424
Предмет: Математика,
автор: Аноним